2002
DOI: 10.1002/mds.10288
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile parkinsonism as a manifestation of systemic lupus erythematosus: Case report and review of the literature

Abstract: Involvement of the central nervous system in systemic lupus erythematosus (SLE) has been well described. It usually includes psychiatric disturbance, seizures, and cranial nerve disorders. Movement disorders are less common, chorea being the one most frequently described. A parkinsonian syndrome may be an extremely rare manifestation of cerebral lupus. We report on a case of juvenile parkinsonism as a manifestation of SLE and review the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 21 publications
0
42
3
Order By: Relevance
“…3 In fact, juvenile parkinsonism (mainly the rigid-akinetic form), despite rare and not included in the 19 neuropsychiatric syndromes defined by the American College of the Reumatology (ACR), 4 is a known manifestation of SLE. 5 In our patient, however, there was no clear evidence that arthralgias were due to arthritis, the psychotic episode was associated with a severe neurological involvement, and the anemia was not hemolytic. Thus, none of these three findings should be considered as diagnostic criteria of SLE according to the ACR.…”
Section: Discussioncontrasting
confidence: 61%
“…3 In fact, juvenile parkinsonism (mainly the rigid-akinetic form), despite rare and not included in the 19 neuropsychiatric syndromes defined by the American College of the Reumatology (ACR), 4 is a known manifestation of SLE. 5 In our patient, however, there was no clear evidence that arthralgias were due to arthritis, the psychotic episode was associated with a severe neurological involvement, and the anemia was not hemolytic. Thus, none of these three findings should be considered as diagnostic criteria of SLE according to the ACR.…”
Section: Discussioncontrasting
confidence: 61%
“…18 A plausible explanation could be that this might represent differing stages of altered blood-brain barrier function within the basal ganglia during active lupus. Alternatively, it 3 Shahar et al 16 may reflect an increased metabolism in the basal ganglia. Lastly, the increased perfusion could be attributed to a drug effect, our SPECT study having been performed a few days after commencement of steroids and cyclophosphamide.…”
Section: Discussionmentioning
confidence: 95%
“…Thus the EEG could be used as a functional monitor, as proposed. 3 Only three out of seven cases showed abnormal neuroimaging (MRI/CT). The role of MRI / CT scans is still unclear as changes in the basal ganglia are inconsistent.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3 Since then, only about 30 NPSLE cases with parkinsonism have been reported to date (Table 1). [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Autoantibodies and immune-mediated vasculopathy was suggested in the pathogenesis of parkinsonism in NPSLE. 20 Kunas et al 4 found antibodies to dopaminergic cells in serum from the NPSLE patients manifested with parkinsonism.…”
Section: Discussionmentioning
confidence: 99%